Current status and solutions for the overuse of emergency CT in pediatric patients with abdominal pain - Weng, Wei; Chen, Yaomeng (Frontiers in Pediatrics, 2025)
Pediatric abdominal pain is one of the most common issues reported in emergency departments (EDs), where emergency computed tomography (CT) plays a crucial role in diagnosing various conditions. However, the frequent use of emergency CT scans in children has raised significant concerns due to the associated risks of unnecessary radiation exposure and increased healthcare costs. This review aims to explore the current situation regarding the overuse of emergency CT scans among children with abdominal pain, examining the factors that contribute to this trend and its harmful effects. It also summarizes recommended interventions and research advancements designed to tackle this issue. By thoroughly reviewing the existing literature, this article seeks to provide valuable insights for clinical practice, promoting the careful use of emergency CT and emphasizing the role of non-ionizing alternatives such as ultrasound and magnetic resonance imaging (MRI) to minimize unnecessary radiation exposure and optimize the use of medical resources.